ANALYSIS OF USING TRANSPORT INFRASTRUCTURE OPPORTUNITIES IN SUSTAINABLE DEVELOPMENT OF UZBEKISTAN'S ECONOMY (Marketing Journal, 2025)
This article provides an analysis of the state of use of transport infrastructure opportunities in the sustainable development of our countryʼs economy. It also provides conclusions and suggestions for an effective analysis of the state of use of transport infrastructure opportunities.
Keywords: region; regional economy; transport; infrastructure; transport infrastructure; state; analysis